2015
DOI: 10.1007/s40609-015-0025-1
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Assets for the Most Vulnerable: the Potential for Asset-Based Interventions

Abstract: In sub-Saharan Africa (SSA), social and economic interactions are governed by both formal (statutory laws, policies, and regulations) and informal institutions (customary laws, social expectations, and religious tenets). When customary and statutory laws misalign, when regressive customary laws are enforced, or when statutory laws are weakly enforced, marginalized groups including children, women, and those impacted by HIV become especially susceptible to economic disenfranchisement predominantly through the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The World Bank report by Larossi et al (2011) showed that having access to financial credits allows women to procure shelter for their families and helps reduce homelessness. However, this is not the case as many women in Sub-Saharan Africa are restricted from owning assets such as houses and lands and tend to hold more non-income-producing assets (Kagotho, 2015;Oladokun et al, 2018). Data showed that the percentage of house ownership among women was 4.82% and 7.06% in the North-East and South-East of Nigeria (National Population Commission, NPC and ICF International, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The World Bank report by Larossi et al (2011) showed that having access to financial credits allows women to procure shelter for their families and helps reduce homelessness. However, this is not the case as many women in Sub-Saharan Africa are restricted from owning assets such as houses and lands and tend to hold more non-income-producing assets (Kagotho, 2015;Oladokun et al, 2018). Data showed that the percentage of house ownership among women was 4.82% and 7.06% in the North-East and South-East of Nigeria (National Population Commission, NPC and ICF International, 2014).…”
Section: Introductionmentioning
confidence: 99%